From intravenous to enteral ketogenic diet in PICU: A potential treatment strategy for refractory status epilepticus. (November 2016) - Chiusolo, F.; Diamanti, A.; Bianchi, R.; Fusco, L.; Elia, M.; Capriati, T.; Vigevano, F.; Picardo, S.
Abstract: Background: Ketogenic diet (KD) has been used to treat refractory status epilepticus (RSE). KD is a high-fat, restricted-carbohydrate regimen that may be administered with different fat to protein and carbohydrate ratios (3:1 and 4:1 fat to protein and carbohydrate ratios). Other ketogenic regimens have a lower fat and higher protein and carbohydrate ratio to improve taste and thus compliance to treatment. We describe a case of RSE treated with intravenous KD in the Pediatric Intensive Care Unit (PICU). Case report: An 8-year-old boy was referred to the PICU because of continuous tonic-clonic and myoclonic generalized seizures despite several antiepileptic treatments. After admission he was intubated and treated with intravenous thiopental followed by ketamine. Seizures continued with frequent myoclonic jerks localized on the face and upper arms. EEG showed seizure activity with spikes on rhythmic continuous waves. Thus we decided to begin KD. The concomitant ileus contraindicated KD by the enteral route and we therefore began IV KD. The ketogenic regimen consisted of conventional intravenous fat emulsion, plus dextrose and amino-acid hyperalimentation in a 2:1 then 3:1 fat to protein and carbohydrate ratio. Exclusive IV ketogenic treatment, well tolerated, was maintained for 3 days; peristalsis then reappeared so KD was continued by the enteral route at 3:1 ratio. Finally, after 8 days and no seizure improvement, KD was deemed unsuccessful and was discontinued. Conclusions: Our experience indicates that IV KD may be considered as a temporary "bridge" towards enteral KD in patients with partial or total intestinal failure who need to start KD. It allows a prompt initiation of KD, when indicated for the treatment of severe diseases such as RSE. Highlights: Ketogenic Diet (KD) is a therapeutic option for status epilepticus (SE). In pediatric intensive care unit treatments for SE may induce intestinal failure. The temporary intestinal failure in SE can require to start intravenous KD. Intravenous KD is resulted in our experience safe and well tolerated. Intravenous KD can be considered as a temporary "bridge" towards enteral KD.